Uso de metronidazol y albendazol en el tratamiento de nemátodos en Corydoras virginiae (Burgess, 1993) - Rodriguez Mendoza, Astrid Caroline (2021)
The fish of the Callichthyidae family are highly demanded in the international market, constituting an important volume of the species that are exported by the commercial aquariums of the city of Iquitos. Parasitic diseases are very common affecting fish, highlighting nematode infections, which if not combated correctly can lead to the death of the fish. Currently there are no studies related to the treatment of species of the Callichthyidae family parasitized by intestinal nematodes, therefore the present study aims to evaluate different doses of Metronidazole and Albendazole to treat infections caused by Nematodes present in Corydoras virginiae. This study was carried out at the Peruvian Amazon Research Institute (IIAP) km 4.5 of the Iquitos - Nauta highway in the Parasitology and Aquaculture Health laboratory, with a duration of approximately 06 months, from (July 19 to July 21). December 2018). The fish were collected from the natural environment and collected by the AQUATRADE commercial aquarium to later be transferred to the IIAP Parasitology and Aquaculture Health Laboratory. An initial sample of analyzed fish revealed the presence of the nematode Procamallanus (Spirocamallanus) pintoi parasitizing the intestine of the C. virginiae specimens. Additionally, morphometric data were taken from male and female specimens of the parasite. Later, infected fish were selected and placed in experimental units to be subjected to different experiments using albendazole and metronidazole for their treatments. Four experiments were carried out: experiment 1. Efficacy of 5g of Albendazole and Metronidazole per kg of food, experiment 2. Efficacy of 10g of Albendazole and Metronidazole per kg of food, experiment 3. Efficacy of 20g of Albendazole and Metronidazole per kg of food and experiment 4. Efficacy of 25g of Albendazole and Metronidazole per kg of feed. Parasitic indices showed that albendazole and metronidazole are effective for the treatment of infections by the nematode P. (S.) pintoi, noting parasite reductions proportional to the days of treatment, in this sense, while the fish were more exposed to the treatment they were noted greater efficacy reflected in a reduction in parasitic prevalences.